A framework of critical success factors for the implementation of maintenance management practices at Public Universities: case study UiTM Perak Campus Seri Iskandar) / Muhammad Hakim Nordin and Alia Abdullah Saleh - Nordin, Muhammad Hakim; Abdullah Saleh, Alia (2023)
Maintenance management is defined as the process of maintaining the assets and resources of a company, which has as main objective to control and reduce costs, times, and resources. Critical Success Factor (CSFs) has been significantly used to present or identify a few key factors that organizations should focus on to be successful. This paper presents a Framework of Critical Success Factors for The Implementation of Maintenance Management Practices at UiTM Perak Campus Seri Iskandar. Aim and objective has been set in order to achieve the study. The purpose of this research is studying critical success factors (CSFs) for the implementation of maintenance management practices at UiTM Seri Iskandar. The objectives for this research is to identify and develop a framework of Critical Success Factors (CSFs) for the maintenance management practice in UiTM Seri Iskandar. the result and findings of the research was carried out by using quantitative data collection. The distribution of questionnaire was sent to maintenance department in UiTM Seri Iskandar. The result based on the analysis and finding in chapter 4 had given the conclusion that most of the respondents know that the implementation CSFs of maintenance management practices in UiTM Seri Iskandar. In the nutshell, the findings of the research study on this topic lead to the best framework for maintenance management at UiTM Seri Iskandar at the same time can have a good impact in the maintenance work.